Pendampingan Pasien Tuberkulosis melalui Penerapan Aplikasi Zero TB Berbasis Patnership Community System: Supporting Tuberculosis Patients through the Application of Zero TB Application Based on Patnership Community System in Surabaya - Subkhan, Mohammad; Firman, Firman; Husna, Anis Rosyiatul; Rosadi, Aswin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Indonesia is ranked third with the most significant number of pulmonary TB (Tuberculosis) patients in the world, after China and India. In 2017, there were 420,994 new TB cases in Indonesia. The survey showed that 68.5% of male participants smoked, while only 3.7% of female participants smoked. This service activity aims to assist TB patients through the Zero TB application based on a community partnership system for TB prevention and treatment. The training effectively improved participants' knowledge, behavior, and compliance. There was a significant change in the level of expertise, where the pre-test results showed that 50% of respondents had low knowledge, but after counseling using the Zero TB application, 83.4% had high knowledge. Behavioral changes also improved, with 53.3% of respondents showing good changes in the pre-test, which increased to 100% after the intervention. The level of treatment adherence also increased from 93.3% of respondents with low adherence in the pre-test to 96.6% with high adherence in the post-test. It is hoped that participants' increased knowledge, behavior, and adherence can prevent TB while raising public awareness of the importance of TB treatment, especially at Yayasan Bhanu Yasa Sejahtera (YABHYSA).